PSIKOLOGI TOKOH BIMO DALAM NOVEL MENGGAPAI MATAHARI KARYA DERMAWAN WIBISONO: Pendekatan Psikologi Sastra - Najamudin, Najamudin; Ayu, Putri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to describe the building elements in the novel Reaching for the Sun by Dermawan Wibisono and Describe the psychology of the character Bimo in the novel Menggapai Matahari by Dermawan Wibisono. The research method uses qualitative descriptive with a content analysis approach in the form of the novel Menggapai Matahari by Dermawan Wibisono In this study focused on personality structures, namely id, ego and super ego. The data collection technique is carried out by reading and recording important information contained in the novel Menggapai Matahari by Dermawan Wibisono, the results of the study show that (1) the intrinsic elements of the novel Menggapai Matahari consist of (a) themes, namely a child who is trying to break the prediction that he will one day trouble his parents. ( b) plot, using the forward plot (c) characterization, starting from Bimo as the main character and several other additional characters (d) the setting, namely the setting of the place, namely in ungaran, the setting when the author tells more about the story from the past continuing to the present, the social setting about the belief in ancient Javanese prophecies, the setting of the atmosphere, depicting a sad atmosphere and a mixed emotional atmosphere of happiness. (e) a first-person point of view (f) the mandate never precedes almighty destiny. (2) personality structures in the form of id, ego and super ego of the psychoanalyst sigmund freud